2017
DOI: 10.3390/nu9091019
|View full text |Cite
|
Sign up to set email alerts
|

The 1-Week and 8-Month Effects of a Ketogenic Diet or Ketone Salt Supplementation on Multi-Organ Markers of Oxidative Stress and Mitochondrial Function in Rats

Abstract: We determined the short- and long-term effects of a ketogenic diet (KD) or ketone salt (KS) supplementation on multi-organ oxidative stress and mitochondrial markers. For short-term feedings, 4 month-old male rats were provided isocaloric amounts of KD (n = 10), standard chow (SC) (n = 10) or SC + KS (~1.2 g/day, n = 10). For long-term feedings, 4 month-old male rats were provided KD (n = 8), SC (n = 7) or SC + KS (n = 7) for 8 months and rotarod tested every 2 months. Blood, brain (whole cortex), liver and ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 53 publications
3
41
1
Order By: Relevance
“…This is consistent with previous work [33] in which similar findings were found in the mixed gastrocnemius of rats fed a ketogenic diet for 8 weeks. Despite the reduction in citrate synthase activity, red quadriceps muscles from KETO-fed rats had increased respiration, perhaps evidence of a compensatory mechanism.…”
Section: Discussionsupporting
confidence: 94%
“…This is consistent with previous work [33] in which similar findings were found in the mixed gastrocnemius of rats fed a ketogenic diet for 8 weeks. Despite the reduction in citrate synthase activity, red quadriceps muscles from KETO-fed rats had increased respiration, perhaps evidence of a compensatory mechanism.…”
Section: Discussionsupporting
confidence: 94%
“…Since there are abundant studies reporting ALT, AST, LDH and CK being closely correlated with exercise time, thus, this will not be elaborated about it here. In another animal study, short- and long-term KD-feeding improved several liver oxidative stress markers, showing that the anti-oxidative potential of KD may also enhance endurance exercise [ 58 ]. Muscular fat oxidation capacity may also play a key role during endurance exercise, and the mechanism of this needs further study [ 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…The aforementioned study also demonstrated state 4 mitochondria respiration was decreased with calorie restriction in the brain, heart, and kidney tissues [18] . Additionally, our lab previously reported an increase in liver total antioxidant capacity and increased antioxidant glutathione peroxidase (GPX) liver protein levels after an 8-month long KD diet in rats [19] . In addition, Newman et al.…”
Section: Introductionmentioning
confidence: 98%